Comparison of MultiColor fundus imaging and colour fundus photography in the evaluation of epiretinal membrane. Issue 4 (22nd November 2018) - Song, Ji Hun; Moon, Ka Young; Jang, Seran; Moon, YeoRae
Abstract: Purpose: To compare MultiColor fundus imaging (MC) and colour fundus photography (CFP) for the evaluation of epiretinal membrane (ERM). Methods: In this retrospective study, 192 eyes (181 patients) that underwent vitrectomy for ERM were imaged using Spectralis optical coherence tomography (for MC) and AFC‐210 digital camera (for CFP) 1 week before vitrectomy. Two investigators independently determined the rate of delineability and ERM area for each modality. Results: The intergrader agreement rates for delineability were very high for both image modalities. The rate of delineability of ERM (%) was higher for MC than for CFP, for both investigators [70.8% versus 52.6% and 73.4% versus 53.6% (both p –)]. Epiretinal membrane (ERM) area measurement showed high agreement between investigators for MC (p = 0.466) but differed significantly between the investigators for CFP (p –). The ERM area determined on MC was significantly wider than that on CFP for both investigators (p – for investigator 1 and p – for investigator 2). Conclusion: The ERM area is more clearly detectable and widely demarcated in MC than in CFP images. MultiColor imaging (MC) may be more sensitive and accurate for early detection of ERM and ERM area measurement.